Skip to main content

Suma de Fracciones-Soluciones


\frac{1}{2}+\frac{1}{3}+\frac{1}{4}

 

  • \frac{1}{2}+\frac{1}{3}+\frac{1}{4}=\left ( \frac{1}{2}+\frac{1}{3} \right )+\frac{1}{4}

 

  • \frac{1}{2}+\frac{1}{3}=\frac{3}{2\cdot 3}+\frac{2}{3\cdot 2}=\frac{5}{6}

 

  • \frac{5}{6}+\frac{1}{4}=\frac{20}{6\cdot 4}+\frac{6}{4\cdot 6}=\frac{26}{24}=\frac{13}{12}

 

 

3+\frac{2}{3}+\frac{x}{2}

 

  • 3+\frac{2}{3}+\frac{x}{2}=\left ( \frac{3}{1}+\frac{2}{3} \right )+\frac{x}{2}

 

  • \frac{3}{1}+\frac{2}{3}=\frac{9}{1\cdot 3}+\frac{2}{3\cdot 1}=\frac{11}{3}

 

  • \frac{11}{3}+\frac{x}{2}=\frac{22}{3\cdot 2}+\frac{3x}{2\cdot 3}=\frac{3x+22}{6}

 

 

\frac{z^{2}}{3}+\frac{z^{2}}{x}

 

  • \frac{z^{2}}{3}+\frac{z^{2}}{x}=\frac{xz^{2}}{3\cdot x}+\frac{3z^{2}}{x\cdot 3}=\frac{z^{2}\left ( x+3 \right )}{3x}